Decoupling “Cling-Cover-Capture” Triple Effects on Stable Zn Anode/Electrolyte Interface - Zong, Quan; Yu, Yifei; Liu, Chaofeng; Zhang, Qilong; Wei, Guoying; Wang, Jiangying; Zhang, Jingji; Cao, Guozhong (ACS nano, 2024)
The electrochemical performance of the Zn anode in a water-based electrolyte is influenced by the Zn anode/electrolyte interface. In the present work, a distinctive interfacial chemistry is enabled by introducing synergistic “cling-cover-capture” effects of different components in aspartame (APM) molecule, which can be described in detail as clinging to the surface of Zn anode by incompletely coordinated nitrogen and oxygen atoms in the main chain, covering the surface by the benzene rings and capturing Zn2+ by the side chains. Benefiting from its triple effects, this steady anode/electrolyte interface homogenizes Zn2+ flux and excludes interfacial active water, thus effectively suppressing both dendrite growth and side reactions. Consequently, the stability and reversibility of Zn anode experience an enhancement, leading to a long cycle lifespan of 5100 h at 1 mA cm–2 and 1 mA h cm–2, and an average Coulombic efficiency of 99.73% at 1 mA cm–2 and 0.5 mA h cm–2 over 1600 cycles. The improved rate capability and cycling durability of Zn||NH4V4O10 full cells further confirm the important role of APM in stabilizing the Zn anode.